Dynamics of self-control during choice and post-choice consumption quantity - Oh, Ga-Eun; Mukhopadhyay, Anirban (Frontiers in Psychology, 2024)
Observed choices between options representing a relative vice and a relative virtue have 13 commonly been used as a measure of eating self-control in the literature. However, even though 14 self-control operations may manifest across the post-choice consumption stage, either similarly 15 or in different ways from the choice stage, most prior research has ignored consumption quantity 16 of the chosen option. While the behavior of choosing a virtue instead of a vice does manifest 17 self-control, we examine how this plays out in post-choice consumption. Specifically, we find 18 that when processing resources are limited, after having chosen a virtue food, unrestrained eaters 19 ironically consumed greater quantities and therefore more calories than restrained eaters (Study 20 1). This reflects more persistent self-control in the post-choice consumption stage among 21 restrained eaters than unrestrained eaters, and occurs because choosing a virtue lowers 22 accessibility of the self-control goal among unrestrained eaters relative to restrained eaters 23 (Study 2), thereby increasing intake of the virtuous food. In contrast, subsequent to having 24 chosen a vice, unrestrained eaters and restrained eaters did not show any such difference in 25 intake (Study 1) or goal accessibility (Study 2). Together, these results reveal that persistence of 26 self-control in the post-choice consumption stage depends on individuals' dietary restraint and 27 their initial exercise of self-control in the choice decision. The mere act of choosing a virtue 28 satisfies unrestrained eaters' self-control goal and leads to increased food intake, whereas the 29 same act keeps the same goal activated among restrained eaters who reduce intake of the chosen 30 virtue. Put differently, persistent self-control across choice and quantity decisions is observed 31 only when those with a dietary goal show successful self-control enactment in the choice stage. 32We therefore highlight that the operation of self-control can be dynamic within a consumption 33 episode, and thus, choice and post-choice quantity are both informative of self-control. 34